A Causal Model of Thriving at Work in Chinese Nurses - Xiaoling Zhu (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
Nursing shortages and nurses’ ability to thrive in their work environments are critical issues affecting the nursing profession. In order to meet the needs of a constantly changing health environment and retain qualified nurses, nurses’ ability to thrive at work is critical for organizational growth and nurses’ self-development. This study identified the variables of predicting thriving at work and developed a causal model for thriving at work in Chinese nurses. The sample was 565 nurses from five general hospitals in Dali city, China. Using stratified random sampling, data were collected from April to September 2019 using seven instruments: Thriving at Work Scale, Psychological Capital Questionnaire, Survey of Perceived Organizational Support, Authentic Leadership Questionnaire, Workplace Mindfulness Scale, Workplace Violence Scale, and Organizational Justice Scale, with the Cronbach’s Alpha ranging from 0.78 to 0.96. The SPSS Program was used to analyze the demographic characteristics of participants, relationships of variables, and distributional characteristics of the data. The model was constructed and tested by using AMOS program. The findings revealed that: There were five predicting variables providing significant linear relationships to and direct and indirect effects to thriving at work, including workplace mindfulness, authentic leadership, workplace violence, organizational justice, and years of experience. Also, psychological capital and perceived organizational support correlated significantly with thriving at work and mediated the effects between predicting variables to the outcome. The final model significantly explained 68.2% of the variance of thriving at work. The results revealed that the modified model fit the empirical data with acceptable fit indices (p< 0.001, χ 2/df = 1.236, RMSEA= 0.020, GFI =0.913, CFI = 0.985, and PGFI = 0.824). Based on the results, a guideline for nursing administration is provided to improve nurses’ thriving at work by building fair, supportive, and safe working environments, improving head nurses’ authentic leadership, and cultivating nurses’ mindfulness. It also suggests that policies should be promulgated to improve and regulate the nurse-patient ratio and to eliminate violence against healthcare professionals in China.